(untitled) (Journal of Partial Differential Equations, 2020)
A time dependent electrochemical machining problem, in which the cathode is fed towards the anode with a constant velocity, is studied. We prove the existence and uniqueness of the weak solution for the problem under the assumption that the cathode is C^1+β for some β ∈ (0,1).